Antibody–Drug Conjugates with Pyrrole‐Based KSP Inhibitors as the Payload Class. Issue 46 (15th October 2018) - Lerchen, Hans‐Georg; Wittrock, Sven; Stelte‐Ludwig, Beatrix; Sommer, Anette; Berndt, Sandra; Griebenow, Nils; Rebstock, Anne‐Sophie; Johannes, Sarah; Cancho‐Grande, Yolanda; Mahlert, Christoph; Greven, Simone; Terjung, Carsten
Abstract: The number of cytotoxic payload classes successfully employed in antibody–drug conjugates (ADCs) is still rather limited. The identification of ADC payloads with a novel mode of action will increase therapeutic options and potentially increase the therapeutic window. Herein, we describe the utilization of kinesin spindle protein inhibitors (KSPi) as a novel payload class providing highly potent ADCs against different targets, for instance HER‐2 or TWEAKR/Fn14. Aspects of technical optimization include the development of different linker attachment sites, the stabilization of ADC linkage to avoid payload deconjugation and finally, the tailor‐made design of active metabolites with a long lasting intracellular exposure in the tumor matching the mode of action of KSP inhibition. These KSPi‐ADCs are highly potent and selective in vitro and demonstrate in vivo efficacy in a broad panel of tumor models including complete regressions in a patient‐derived urothelial cancer model. Abstract : Flexible, stable, potent : Inhibitors of kinesin spindle protein (KSP) have been developed as a novel payload class in antibody–drug conjugates (ADCs) with the goal to increase the therapeutic window. Flexibility in linker attachment and tuning of the profile of active metabolites matching the KSPi mode of action as well as high linker stability provide potent ADCs against different targets.